Effects of aluminum on the elongation and external morphology of root tips in two maize genotypes - Leandro Torres de Souza (Bragantia, 2016)
The objective of this study was to evaluate the effects of toxic levels of aluminum (Al) on the growth and external morphology of root tips in two maize genotypes with differential Al tolerance. The maize genotypes UFVM-100 (Al-sensitive) and UFVM-200 (Al-tolerant) were treated with 0 and 50 μM Al in a 0.5 mM CaCl2 solution at pH 4.5; root elongation, Al content and the external morphology of the root tips were evaluated. Chemical analysis, hematoxylin staining and energy dispersive X-ray spectrometry (EDS) showed greater Al accumulation in the root tips of the UFVM-200 genotype. The inhibition of root elongation in the UFVM-100 genotype, however, was much stronger than in the UFVM-200 genotype. Both maize genotypes exhibited visible and intense alterations in external micromorphology of the root tip, especially the Al-sensitive UFVM-100 genotype. Scanning electron micrographs showed intense cell disorganization and transverse ruptures of the protodermic and outer cortex layers of the cells in both genotypes. The ruptures were deeper and wider and reached the inner cortex layers in the UFVM-100 genotype. The EDS analysis showed that, in addition to Al accumulation, there was a proportional increase in the P concentration in the root tips of the UFVM-200 genotype. This is indicative of possible precipitation and/or immobilization of Al in the root tip apoplast of this genotype, which contributes to symplastic detoxification.